An analysis of tax inspections efficiency in countering the grey area in trade — a case of the Internet - Ćwiąkała-Małys, Anna; Nowakowska-Kempna, Iwona (Wydawnictwo Uniwersytetu Wrocławskiego, 2012)
For years there have been actions taken to reduce the grey area in economy. Not only the number of inspections and their frequency have increased but also their efficiency which is counted on the basis of detected irregularities — tax reductions. The efficiency of actions taken in the opinion of entrepreneurs is low and in Supreme Chamber of Control’s opinion it is still in constant evolution. The biggest problem is the lack of intensive cooperation between controlling authorities of various levels and a central tax system.
Keywords: analysis of tax inspections efficiency; countering the grey area; grey area; trade; Internet